Hallux sesamoid fractures in young athletes - Stein, C. J.; Sugimoto, D.; Slick, N. R.; Lanois, C. J.; Dahlberg, B. W.; Zwicker, R. L.; Micheli, L. J. (The Physician and Sportsmedicine, 2019)
Objective: To describe the evaluation, management and recovery time of hallux sesamoid fractures in young athletes.